Translation and psychometric testing of the Chinese version of the Perinatal Missed Care Survey - Shenglan Ding; Xin Wang; Qingxia Wang; Juan Shen; Huili Xie; Xiujuan Fu; Luxi Liao; Jiaojiao Chen; Lian Zhu; Jing Huang; Siyuan Yang; Xiuhua Huang; et al. (Elsevier, 2024)
Objective: This study aimed to translate and evaluate the psychometric properties of the Perinatal Missed Care Survey in China. Methods: The Perinatal Missed Care Survey was translated according to the guidelines of the cross-cultural debugging scale recommended by the American Academy of Orthopaedic Surgeons Evidence-Based Medicine Committee, including forward translation, back translation, cultural adaption, and content validation, and its Chinese version was used in a cross-sectional study conducted from February to April in 2023. A total of 491 midwives from 14 different level hospitals in southwest China were recruited through a convenience sampling method. The discrimination ability of the items was tested through item analysis, and construct validity was assessed through exploratory factory and confirmatory factor analyses. The content validity index and Cronbach's α coefficients evaluated content validity and reliability, respectively. Results: The Chinese version's item-total correlation coefficients ranged from 0.641 to 0.866 in part A and from 0.644 to 0.819 in part B (P < 0.001). Parts A and B's scale-level content validity indexes were 0.95, and the item-level content validity indexes were from 0.86 to 1.00. The three common factors of part A (necessary care, basic care, and postnatal care) and part B (communication, labor resources, and material resources) were extracted, accounting for 70.186% and 71.984% of the total variance, respectively. Confirmatory factor analysis indicated that the good fit of the three-factor models was acceptable. The Cronbach's α coefficients were 0.968 (part A) and 0.940 (part B). Conclusion: The Chinese version of the Perinatal Missed Care Survey is a reliable and valid instrument for assessing nursing care missed by midwives during labor and birth and the reasons it was missed. Studies with large sample sizes are needed to verify the instrument's applicability in China.